LncRNA KCNQ1OT1 predicts further cerebral events in patients with transient ischemic attack - Shijia Yu; Jing An; Ran Sun; Juan Feng; Mingjun Yu (Frontiers Media S.A., 2022)
Transient ischemic attack (TIA) poses a great threat of cerebrovascular diseases to a large number of patients, despite its reversible neurological dysfunction. Long non-coding RNAs (lncRNAs) have been proven to play critical roles in the pathophysiological development of cerebrovascular events. Exploring the function of lncRNAs in modulating TIA prognosis would help to develop individualized therapeutics. A total of 231 participants with the first onset of TIA were recruited in the study, including 65 subsequent stroke patients. The expression of lncRNA potassium voltage-gated channel subfamily Q member 1 opposite strand 1 (KCNQ1OT1) was upregulated in patients with recurrent ischemic events after TIA. Additionally, KCNQ1OT1 could be regarded as an independent predictor for subsequent ischemic stroke. The optimal diagnostic value was determined at 1.29 with a sensitivity of 63% and a specificity of 72%. Fewer patients would survive from further ischemic stroke with their KCNQ1OT1 level over 1.29. Furthermore, the expression of KCNQ1OT1 was elevated with a growing serum high-sensitivity C-reactive protein (hs-CRP) level. KCNQ1OT1 might be involved in the regulation of early inflammatory response during recurrence of TIA.